The diagnostic accuracy of 68 Ga-PSMA-PET/CT in primary staging of patients with high-risk nonmetastatic prostate cancer treated with radical prostatectomy: A single-center cohort analysis - Rajwa, Pawel; Heidenreich, Julian; Drzezga, Alexander; Schmidt, Matthias; Shariat, Shahrokh F; Heidenreich, Axel (The Prostate, 2024)
BACKGROUND: 68 Ga-prostate-specific membrane antigen (PSMA) positron emission tomography (PET)/computed tomography (CT) is a recommended imaging modality for patients with recurrent prostate cancer (PCa). Its routine implementation before radical prostatectomy (RP) may allow avoiding undertreatment. We aimed to analyze the diagnostic accuracy of 68 Ga-PSMA-PET/CT for pelvic lymph node metastases in a large cohort of patients treated with RP and extended pelvic lymph node dissection (ePLND) for high-risk PCa. METHODS: This is a retrospective analysis of an institutional database of patients who underwent 68 Ga-PSMA-PET/CT before RP and ePLND for high-risk PCa. The diagnostic estimates of 68 Ga-PSMA-PET/CT with 95% confidence intervals (CIs) for lymph node involvement were calculated. RESULTS: We included 165 high-risk PCa patients. The median PSA value was 24.5 ng/mL (range: 6.7-185) and all the patients had biopsy Grade Group 4-5. In total, 46 (28%) of patients had clinical lymph node involvement at 68 Ga-PSMA-PET/CT. A mean number of resected lymph nodes per patient was 22 (range: 15-45) and 149 (4.2%) of all resected nodes were positive for lymph node metastasis at final pathology. The diagnostic estimates for the detection of pN+ disease at RP were as follows: sensitivity 63% (95% CI: 51-75), specificity 97% (95% CI: 91-99), positive predictive value 94% (95% CI: 82-99), and negative predictive value 79% (95% CI: 70-86). The total accuracy of PSMA-PET was 83% (95% CI: 76-88). CONCLUSION: Our analyses support high specificity and positive predictive value of pretreatment 68 Ga-PSMA PET/CT for the detection of pelvic lymph node metastasis in patients treated with RP for high-risk PCa. While a positive finding should be considered as robust indicator for clinical decision-making, a negative result cannot reliably rule out the presence of lymph node involvement in high-risk PCa; there is a need for advanced risk stratification in those patients.
Keywords: Prostatic Neoplasms; nonmetastatic; prostata; nádory prostaty; Humans; lidé; Lymphatic Metastasis; lymph node dissection; prostate cancer; Prostatectomy; lymfatické metastázy; staging nádorů; Male; Prostate; radical prostatectomy; Positron Emission Tomography Computed Tomography; Retrospective Studies; retrospektivní studie; Neoplasm Staging; prostatektomie; lokální recidiva nádoru; radioizotopy galia; Gallium Radioisotopes; PSMA PET; mužské pohlaví; Neoplasm Recurrence, Local; PET/CT